Turbidity and TSS removal from textile wastewater using a combination of natural and chemical coagulants - Noor Shakir Ali; Ali Jwied Jaeel (Wasit Journal of Engineering Sciences)
Abstract: Recently natural coagulants are a consistently expanded; plants extracted coagulant which may be adopted in the coagulation-flocculation activity of textile wastewater treatment for reduction concentration of turbidity and total suspended solids. In this study, the possibility of a combination between chemical coagulant (alum) and natural plant coagulant (Capparis Spinosa) in excluding turbidity and total suspended solids from textile wastewater has been studied. A set of experiments were implemented for verifying the turbidity and TSS removal efficiency using alum and powder extracted from Capparis Spinosa plant separately. A combined dosage consisted of chemical coagulant (alum) dosages (10, 20, 30 and 40 mg/l) with natural coagulant dosages (10, 20, 30 and 40 mg/l) in order to detect the optimum combined percentage of both coagulants (alum and Capparis Spinosa) that produces higher removal efficiencies for both turbidity and TSS. The study found the activity of removal for both turbidity and total suspended solids increased in high performance when mixing is occurred between natural coagulant (Capparis Spinosa) and chemical coagulant (Alum). The results illustrate that the combination of 20 mg/l alum with 30 mg/l Capparis Spinosa made 99% turbidity removal and the combination of 30 mg/l alum with 30 mg/l Capparis Spinosa made 98% TSS removal.